The genus Exogone (Polychaeta: Syllidae) from the Brazilian coast, with the description of a new species - Paresque, Karla; Fukuda, Marcelo Veronesi; Nogueira, João Miguel De Matos (Zootaxa, 2014)
A new species of Exogone, E. gigas sp. n., is described herein, together with E. africana, E. arenosa, E. dispar, E. naidinoides, E. rolani, and E. simplex, collected along the Brazilian coast, including new morphological details. The distribution of E. breviantennata is expanded to include the states of Espírito Santo, Paraíba and Pernambuco. Exogone gigas sp. n. is characterized by having a large median antenna, the absence of dorsal cirri on chaetiger 2, and having a triangular process and minute spines on the shaft of the spiniger-like chaetae on chaetiger 2. The Brazilian specimens are compared to the morphologically most similar congeners. A key for the species described in this paper is provided.